A comparative analysis of kratom exposure cases in Thailand and the United States from 2010-2017 - Christian Davidson (2022)
Background: Interest in the Southeast Asian natural remedy kratom has increased in Western countries recently, along with increasing concern over its potential toxic effects. Objective: To describe and compare demographics, common co-exposure substances, clinical effects, treatments, and medical outcomes of kratom “abuse” exposures in the United States (US) and Thailand. Methods: This is a retrospective analysis of kratom “abuse” exposures, defined as use when attempting to gain a psychotropic effect, reported to the National Poison Data System (NPDS) in the US and the Ramathibodi Poison Center (RPC) in Thailand from 2010 to 2017. Multivariate analysis identified risk factors for severe medical outcomes, defined as both ICU admissions and death. Results: Nine-hundred-twenty-eight cases were included (760 from NPDS and 168 from RPC). A greater proportion of cases involved co-exposures in Thailand (64.8% versus 37.4%; odds ratio [OR] = 3.10, 95% confidence interval [CI] = 2.15–4.47, p < .01). Both countries had a similar prevalence of opioid and benzodiazepine co-ingestions, but the US had more co-ingestions with other sedatives (4.6% versus 0%, OR = 0, 95% CI = 0–0.47, p < .01). Common clinical effects included tachycardia (30.4%), agitation/irritability (26.2%), and drowsiness/lethargy (21.1%). Six deaths occurred, including one single-substance exposure in the US, three multiple-substance exposures in the US, and two multiple-substance exposures in Thailand. Severe medical outcomes were reported more frequently in the US (OR = 18.82, 95% CI = 5.85–60.56, p <.01). Conclusions: Despite lower frequencies of co-ingestants overall, US kratom abuse exposures yielded greater clinical severity. This disparity may be attributable to differences in the products labeled “kratom,” greater sedative co-exposures in the US, and/or differences in population genetics or use patterns.